Ectopic blastema induction by nerve deviation and skin wounding: a new regeneration model in Xenopus laevis. Issue 2 (28th May 2014) - Mitogawa, Kazumasa; Hirata, Ayako; Moriyasu, Miyuki; Makanae, Aki; Miura, Shinichirou; Endo, Tetsuya; Satoh, Akira
<x xml:space="preserve">Abstract</x> We successfully applied the accessory limb model (ALM) of axolotls to Xenopus laevis, a species with a regenerate capacity intermediate between axolotls and higher vertebrates. In contrast to axolotl ALM blastemas, Xenopus ALM‐induced blastemas could not form cartilage unless bone was damaged. The Xenopus ALM model may facilitate the identification of gene expression programs and signaling pathways regulating cartilage, bone, and muscle formation during limb regeneration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>